Fault tolerant fingerprint-based positioning - Michaelides, Michalis P.; Panayiotou, Christos; Laoudias, Christos (My University, 2011)
The increasing demand for indoor location-based services has motivated the development of positioning methods that exploit the existing wireless network infrastructure. Accuracy is an important requirement, however fault tolerance is also highly desirable in case of failures or malicious attacks. We investigate the fault tolerance of fingerprint-based methods under a variety of fault or attack scenarios. We study the Subtract on Negative Add on Positive (SNAP) algorithm and modify it appropriately for the WLAN setup. Our results indicate that SNAP achieves adequate accuracy with very low computational complexity and exhibits smoother performance degradation in the presence of faults compared to other methods. © 2011 IEEE.
Keywords: Fault tolerance; Fault tolerant systems; Accuracy; Wireless LAN; Estimation; IEEE Communications Society; Degradation